Melatonin effect on plasma adiponectin, leptin, insulin, glucose, triglycerides and cholesterol in normal and high-fat fed rats - Ríos Lugo, María J. (2010)
Fil: Ríos Lugo, María J. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España